Borderline hospitality: homestays as a commercial hospitality development project in Grahamstown, Eastern Cape - Von Lengeling, Volkher Heinrich Christoph (Rhodes University, Faculty of Humanities, Department of Anthropology, 2016)
This study started as an anthropological investigation of commercial hospitality from the point of view of the hands-on host. The chosen case study for this investigation was the Kwam eMakana Government Initiated Poverty Alleviation Project which offered homestays in the townships of Grahamstown East since 2004. Homestays are the most intimate form of commercial hospitality, one step removed from non-commercial or social hospitality. Even at the homestay level there is a conceptual conflict between poverty and (Westernized) commercial hospitality, however, Kwam homes are more middle class than poor. Later the investigation revealed the deeper-seated form of poverty of the Kwam participants being (almost) illiterate. Kwam was a development project like many others, in which huge amounts of money were spent in the name of the project but very little of the benefits reached the intended beneficiaries. Thus, as fieldwork ensued, the emphasis of research migrated from an empirical study of homestay hospitality, to actively assist with the struggle of the Kwam hostesses to maintain the project and gain autonomy for themselves. This study was from the outset reflexive, as the host's point of view could technically only be presented by auto-ethnography. Then the investigation shifted to a form of engaged anthropology far exceeding advocacy as it is usually understood. The presentation of this can be called radical reflexivity, while it is simultaneously an ethnographical account in the sense of anthropology 'at home'. It also implied, besides ethical concerns, revisiting literary sensibilities, such as the use of a third person narrative for the reflexive account. To conceptualize the development process of both Kwam and the research interventions Bourdieu's 'totality of capital' (in which the strands of economic, symbolic, cultural and social capitals intertwine) proved most useful. By assessing the various capitals the development of the project and the power struggles central to it can be understood. This study confirms that long-term anthropological investigation is best suited to the study of development projects, if not necessary for real development to be effected. Reflexivity and ethnography are complementary methods to reveal truths which under certain research circumstances may have been very difficult or even impossible to research.
Keywords: Uncatalogued